Meditation on Human Response-Ability - Tran, Mai-Anh Le (Religious education, 2021)
This forum essay offers reflections on the theme of the 2021 annual meeting of the Religious Education Association—“Gender, Sexuality, and Wholeness: Religious Education for Confrontation and Healing.” Pondering the melancholy of violence inflicted upon racialized, sexualized, and queer bodies in the United States, the author invites members of the association and discipline of religious education to que(e)ry the subjects that often remain null in the telos of all education anchored in religion.